2016
DOI: 10.1002/1873-3468.12451
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of the antifreeze activities of active and inactive isoforms of a type III antifreeze protein

Abstract: The quaternary-amino-ethyl 1 (QAE1) isoforms of type III antifreeze proteins (AFPs) prevent the growth of ice crystals within organisms living in polar regions. We determined the antifreeze activity of wild-type and mutant constructs of the Japanese notched-fin eelpout (Zoarces elongates Kner) AFP8 (nfeAFP8) and characterized the structural and dynamics properties of their ice-binding surface using NMR. We found that the three constructs containing the V20G mutation were incapable of stopping the growth of ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…These outcomes are consistent with mutagenesis and computational studies of AFP III, which reported that conserved proline residues contribute to observed antifreeze activity (thermal hysteresis) and protein folding in vivo [36,37] and that ice binding sites in AFPs are predominantly hydrophobic. [10,11,38,39] Our findings are further supported by a recombinant AFP III variant which differed by the inclusion of 2 additional (cationic) lysine residues and 1 additional methionine residue which not only displayed a slightly enhanced IRI activity but also an elevated resistance to thermal degradation. [40] The same study also showed circular dichroism spectroscopy measurements at 0 °C that displayed no significant differences in spectra.…”
Section: [Insert Figure 4]supporting
confidence: 62%
See 1 more Smart Citation
“…These outcomes are consistent with mutagenesis and computational studies of AFP III, which reported that conserved proline residues contribute to observed antifreeze activity (thermal hysteresis) and protein folding in vivo [36,37] and that ice binding sites in AFPs are predominantly hydrophobic. [10,11,38,39] Our findings are further supported by a recombinant AFP III variant which differed by the inclusion of 2 additional (cationic) lysine residues and 1 additional methionine residue which not only displayed a slightly enhanced IRI activity but also an elevated resistance to thermal degradation. [40] The same study also showed circular dichroism spectroscopy measurements at 0 °C that displayed no significant differences in spectra.…”
Section: [Insert Figure 4]supporting
confidence: 62%
“…[9] Within the multitude of protein structures reported, the presence of hydrophobic (proline) amino acid sidechain domains is reported to be of particular importance for the maintenance of iceprotein interactions and IRI activity. [10,11] The reengineering of proteins via de novo gene design, directed evolution or in silico approaches is beginning to allow the prediction of subsequent secondary structure and function. [12] An example of protein surface engineering includes the conversion of surface accessible acidic residues into aminated species (supercharging), resulting in an increase in the isoelectric point.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments showed that the mutants exhibited increased conformational flexibility and were incapable of binding to the primary prism plane of ice crystals. These results suggested that inactive type III AFPs may be unable to anchor water molecules via H-bond interactions in the first 3 10 helix (residues 18–22) and therefore have no antifreeze activity [136]. …”
Section: Marine-derived Afpsmentioning
confidence: 99%